Diagnostic Yield of Pleural Biopsy in Gulab Devi Chest Hospital - GHULAM SHABBIR PERVAIZ, ASIF HANIF, ZAHEER AKHTAR, HAMID HASSSAN (Journal of Fatima Jinnah Medical University, 2018)
Background: Sometimes it is difficult to make diagnosis of pleural effusion on routine investigation such pleural effusion is labeled as undiagnosed exudative pleural effusion. Aim of present study was to see the role of pleural biopsy in the diagnosis of undiagnosed exudative pleural effusion. Objective: To know the diagnostic role of pleural biopsy in determining underlying etiological causes of pleural diseases. Method: A total of 71 patients out of which 50 were male and 21 were female patients, aged 15-80 years with mean age 40 years, underwent closed pleural biopsy with Abram’s needle. Average 3 biopsy specimens were obtained in each patient, which are examined histopathologically. Results: Pleural biopsy was done in 71 patients. Pleural tissue was obtained in 65 (91.5%) cases. Tuberculosis(caceous granuloma) in 33 (46.4%) Malignancy was diagnosed in 16 (22.5%), non-specific inflammation in 12 (16.9%), non caceous granulomatous pleuritis 4 (5.6%) and cases on histopathological examination. Conclusion: pleural biopsy can determine underlying cause of pleural diseases in most of the patients and is a useful diagnostic test in non-conclusive lymphocytic exudative pleural effusion.